2001
DOI: 10.1038/sj.sc.3101185
|View full text |Cite
|
Sign up to set email alerts
|

Single stage decompression, anterior interbody fusion and posterior instrumentation for tuberculous kyphosis of the dorso-lumbar spine

Abstract: Results: The mean kyphosis correction obtained was 62.5% with the mean post-operative kyphosis angle reducing to 24.1 (range 5 ± 60). At a mean follow-up of 5.8 years (4 ± 7 years) the mean kyphosis angle loss was 3.28 (range 0 ± 58). Of the 23 patients with neurological de®cit, recovery was seen in 21 cases (91.3%) while deterioration was seen in one case (4.3%). The remaining ®ve patients were neurologically intact pre-operatively. Bony fusion was seen in all cases at 9 months. One patient with subpulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 21 publications
(8 reference statements)
1
60
0
Order By: Relevance
“…The decompression was adequate as indicated by the neurological recovery in most of the cases in accordance with available literature showing neurological recovery varying from 82 to 95% recovery of ambulatory status [17,18]. Adequate debridement and decompression also makes room for healthy cancellous bone apposition resulting in high fusion rates [19,20]. We did not include patients with multilevel disease or those with severe kyphosis.…”
Section: Discussionmentioning
confidence: 66%
“…The decompression was adequate as indicated by the neurological recovery in most of the cases in accordance with available literature showing neurological recovery varying from 82 to 95% recovery of ambulatory status [17,18]. Adequate debridement and decompression also makes room for healthy cancellous bone apposition resulting in high fusion rates [19,20]. We did not include patients with multilevel disease or those with severe kyphosis.…”
Section: Discussionmentioning
confidence: 66%
“…It is clear that posterior instrumentation is more effective in kyphosis correction and prevention of late-term progression especially in kyphosis with two or more levels of involvement or in moderate or severe kyphosis [12,15,17,26,29]. In a study, Wen-Jer et al [31] has obtained 56% kyphosis correction with two-stage anterior-posterior surgery and reported 3°of correction loss during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Klockner et al [16] suggested that posterior instrumentation should be combined with anterior debridement and fusion in deformities affecting many levels and/or in excessive kyphotic deformities. Laheri et al [17] achieved 62.5% correction performing costotransversectomy and decompression, anterior interbody fusion and posterior instrumentation at the same stage in patients with kyphosis due to tuberculosis with dorsolumbar involvement and reported an average of 3.2°correction loss in kyphosis angle following 5.8 years of follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Following the advent of modern spinal instrumentation systems, several authors have reported combined anterior and posterior fusion either as a single-stage or as a twostage procedure following the initial description of the procedure by Yau et al [12][13][14][15][16][17][18][19][20][21][22][23] in 1974. Earlier apprehensions regarding the use of metal implants in the presence of active tubercular infection were overcome following the realization that tubercle bacilli had slow rates of division, lower bacillary counts than pyogenic infections, and do not produce adhesion molecule and bio-film [24,25].…”
Section: Discussionmentioning
confidence: 99%